Analysis of the factor structure of the Emotional Fatigue Scale, invariance, and validity based on the relationship with other variables in university professors - Renzo Felipe Carranza Esteban; Oscar Mamani-Benito; Ronald Castillo-Blanco; Isabel Cabrera-Orosco; Susana K. Lingán-Huamán (Frontiers in Education)
The objective of this study is to analyze the evidence of validity, factorial invariance, and reliability of the Emotional Fatigue Scale in Peruvian university professors. Instrumental and cross-sectional design research was carried out, with the participation of 604 Peruvian university professors from the three regions of the country (Coast, Highlands, and Jungle) and with ages ranging from 21 to 65 years (M = 44.27 and SD = 9.15), who were selected with the intentional non-probabilistic sampling method. The descriptive analyses of the items were adequate and the polychoric correlation matrix with which the confirmatory factor analysis was performed was adequate. The results show a one-dimensional structure of 9 items, because item 10 had to be eliminated [χ2(27) = 98.7, p < 0.001, CFI = 0.993, RMSEA = 0.067 y SRMR = 0.029]. The resulting factor loads are between 0.57 and 0.93 and the internal consistency is adequate (ω = 0.95). It was also found that the scale presents evidence of invariance according to sex, age, and working hours and of convergent validity with the scales of psychological distress (r = 0.64, p < 0.001) and life satisfaction (r = −0.46, p < 0.001). In conclusion, the ECE-PU is a brief measure that has adequate psychometric properties and is useful to assess emotional exhaustion in Peruvian university professors.